PERANCANGAN MESIN MELTER OTOMATIS UNTUK MENGOLAH SAMPAH PLASTIK MENJADI PAVING BLOCK - nalahuddin, Muchlisi; Sayrief, Fauzi (Jurnal Ilmiah Poli Rekayasa, 2024)
The increasing amount of plastic waste is one of the main challenges in current waste management. One solution that can be implemented is processing plastic waste into value-added products, such as paving blocks. This study aims to design and develop an efficient melting machine for processing plastic waste into paving blocks. The methods used in this research include the design phase using Solidworks 2022, prototyping, and testing of the melting machine. During the design phase, an analysis of the melting machine requirements was conducted, including capacity, operating temperature, and safety aspects. The design of the melting machine was carried out by considering ergonomic aspects, energy efficiency, and the ability to produce high-quality paving blocks. This process involved the use of materials resistant to high temperatures and thermal insulation materials to maintain optimal operating temperatures. The melting machine was then tested under various operational conditions to evaluate its performance. The melting machine must reach the required operating temperature of 200°C to melt plastic waste without damage. PET (polyethylene terephthalate) plastic waste processed into paving blocks has a compressive strength of 11.09 MPa and meets Class D quality standards in accordance with SNI 03-0691-1996